Study on the pathogenesis of varicocele induced by the ferroptosis of cremaster satellite cells with the m6A modification of TFRC mRNA - Zhiqiang Mo; Weiping Zhang; Xianghui Xie; Ning Sun; Jun Tian; Minglei Li; Hongcheng Song (PLoS ONE, 2025)
Background Varicocele (VC) is a leading cause of male infertility. Insufficient growth and development of the cremaster muscle may contribute to VC, but the underlying mechanism remains unclear. Cremaster muscle dysfunction may impair venous valve support, contributing to VC. The cremaster relies on satellite cells (SCs) for postnatal growth and damage repair. This study aimed to explore the mechanism of the cremaster muscle in the process of VC. Methods Ten male Sprague-Dawley (SD) rats were divided into two groups: the VC model group (5 rats) and the sham-control group (5 rats). After four weeks of observation, the cremaster muscles were collected. The diameters of the left and right spermatic veins were measured, and the left testis was isolated for morphological examination via H&E staining. SCs isolated from the left cremaster muscle were analyzed using multiple methods, including qPCR and Western blot. Data were analyzed using SPSS v.22.0. Results Compared to the control group, the model group showed decreased TFRC mRNA stability, decreased mitochondrial membrane potential, and decreased GSH and GSSG contents, as well as increased m6A modification levels and increased ROS, MDA, and Fe2+ contents. In addition, the model group also showed downregulation of transferrin receptor (TFRC, a key iron uptake protein involved in ferroptosis) expression and upregulated m6A methyltransferase and recognition proteins. Multiple biochemical test results indicated increased ferroptosis, characterized by changes such as decreased mitochondrial membrane potential and GSH and increased ROS, MDA, and Fe2+. Conclusion This study suggests that SCs in the cremaster muscle is associated with impaired cremaster muscle repair and VC pathogenesis through m6A modification of TFRC mRNA. Our findings offer fresh insights into the role of cremaster SCs in VC and provide a foundation for future research on the potential therapeutic target of VC. Strengths and limitations of this study This study is the first to investigate the pathogenesis of varicocele from the perspective of the cremaster muscle, and some clues have been discovered from it. The causal relationship between m6A-TFRC axis and ferroptosis requires further validation using functional rescue experiments (e.g., METTL3 knockdown or ferroptosis inhibitors). The small sample size may limit statistical power; future studies with larger cohorts are warranted.